Tulsi (Ocimum sanctum) Leaf Ethanol Extract Reduces Inflammatory Cell Infiltration in Aspirin-Induced Gastritis Rats - Sari, Festi Artika; Sandhika, Willy; Yuliawati, Tri Hartini (Fakultas Kedokteran Universitas Brawijaya, 2020)
Gastritis is an inflammation of the gastric mucosa. Tulsi leaf extract has phenol, flavonoid and saponin compounds which are potential as antioxidant and increase defensive factors in the gastric. The purpose of this research was to find out the effect of tulsi (Ocimum sanctum) leaf extract in polymorphonuclear (PMN) inflammatory cell infiltration in gastric of aspirin-induced gastritis rat model. This study was laboratory experimental research using post-test only control group design. Randomly, 27 male rats were divided into 3 groups, the first group was not induced by aspirin and extract as negative control, the second group was induced by aspirin of 600 mg/kgBW as positive control, and the third group was induced by aspirin of 600 mg/kgBW and was given Ocimum sanctum extract at a dose of 400 mg/kgBW as treatment group. Gastric of the rats were taken on 16th day for histopathology evaluation using hematoxylin and eosin (HE) staining. Evaluation was done by calculating the PMN inflammatory cell infiltration in mucosal and submucosal layer. The results of the average number of PMN inflammatory cell in the gastric tissue of the treatment group showed a significant decrease compared to the positive and negative control groups with P-value <0.05. This study proved that Ocimum sanctum leaf extract administration with the dose of 400 mg/kgBW can decrease gastritis inflammation by reducing PMN inflammatory cell in gastric of aspirin-induced gastritis rat model.